(untitled) (Progressive Agriculture, 2014)
The very virulent infectious bursal disease virus (vvIBDV) infection cause constant and frequent outbreaks of IBD. In order to prevent the disease caused by vvIBDV, moderate-virulent live vaccines are usually used in broilers, but these vaccine influence the immune system of chickens and cause the immunosuppression. VAXXITEK® HVT+IBD bivalent vaccine, a novel vaccine produced by Merial Company, is the recombinant vaccine generated by inserting IBDV VP2 gene into the HVT genome. The recombinant vaccine could prevent Mareks disease and IBD of chickens at the same time after vaccinated by the subcutaneous route at 1-day-old. The objective of this study was to evaluate protection effect of this new vaccine against IBD in broilers. The results of the lab and field immunization trial showed that the vaccination of VAXXITEK® HVT+IBD vaccine did not damage the bursa of broilers; the level of IBD antibody of the VAXXITEK® HVT+IBD vaccination groups was higher than IBD-BLEN® vaccination groups at 21-day-old; the protection effect of the VAXXITEK® HVT + IBD vaccination groups was better than IBD-BLEN® vaccination groups, especially at 21-28 day. The results indicated that VAXXITEK® HVT + IBD vaccine could provide better protection to broiler chickens against IBD. DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19102 Progress. Agric. 24(1&2): 69 - 78, 2013